High resolution mapping of interstitial long arm deletions of chromosome 16: relationship to phenotype. Issue 10 (October 1993) - Callen, D F; Eyre, H; Lane, S; Shen, Y; Hansmann, I; Spinner, N; Zackai, E; McDonald-McGinn, D; Schuffenhauer, S; Wauters, J
Abstract : The breakpoints of seven interstitial deletions of the long arm of chromosome 16 and two ring chromosomes of this chromosome were mapped by in situ hybridisation or by analysis of mouse/human somatic cell hybrids containing the deleted chromosome 16. Use of a high resolution cytogenetic based physical map of chromosome 16 enabled breakpoints to be assigned to an average resolution of at least 1.6 Mb. In general, interstitial deletions involving q12 or q22.1 have broadly similar phenotypes though there are differences in specific abnormalities. Deletions involving regions more distal, from 16q22.1 to 16q24.1, were associated with relatively mild dysmorphism. One region of the long arm, q24.2 to q24.3, was not involved in any deletion, either in this study or in any previous report. Presumably, monosomy for this region is lethal. In contrast, patients with deletions of 16q21 have a normal phenotype. These results are consistent with the proposed distribution of genes, frequent in telomeric Giesma light band regions but infrequent in G positive bands.